Foresight methods in innovation - Mekhovych, K. S. (Харківська державна наукова бібліотека імені В. Г. Короленка, 2024)
The report discusses foresight methods as a tool for strategic planning and management in the field of innovation. Foresight methods include a set of approaches that allow predicting the development of technologies, markets and socio-economic trends, as well as forming strategies to adapt to future changes. The main focus is on the stages of the Foresight process, in particular, the identification of key trends, the formation of scenarios, the assessment of risks and opportunities, the selection of strategies and their adjustment. The importance of foresight methods for increasing the competitiveness of organizations and the development of national policies in the field of innovation is substantiated.

Розглянуто форсайт-методи як інструмент стратегічного планування та управління в сфері інновацій. Вони включають комплекс підходів, що дозволяють передбачати розвиток технологій, ринків і соціально-економічних трендів, а також формувати стратегії для адаптації до майбутніх змін. Основну увагу приділено етапам форсайт-процесу, зокрема, ідентифікації ключових трендів, формуванню сценаріїв, оцінці ризиків і можливостей, вибору стратегій та їх коригуванню. Обґрунтовано значущість форсайт-методів для підвищення конкурентоспроможності організацій та розробки національних політик у сфері інновацій.
Keywords: foresight methods; scenarios; risks; monitoring; trends; opportunities; форсайт-методи; сценарії; ризики; моніторинг; тренди; можливості